Estimation of pitching moment of a hybrid lifting fuselage - Disguised as hull of an airship - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Mohamed Ali, Jaffar Syed (Asian Research Publishing Network, 2016)
Munk-Multhop's method is usually used for estimation of pitching moment of fuselage of conventional aircraft but application of the same for hybrid lifting fuselage had not been earlier explored. CFD methods can also be applied for the said purpose but it is difficult to separate out the portion of the moment caused by the fuselage, since the wing and fuselage affect each other. In the present work, a hull disguised as hybrid lifting fuselage of a hybrid buoyant aircraft was taken as a test case. Slope of the pitching moment obtained from the Munk-Multhop's method was further corrected to account for the effect of slenderness ratio. Good agreement of results was found after defining the camber profile of the hybrid lifting fuselage and applying the said correction. The location of the wing relative to the fuselage and lift curve slope of wings has a dominant role in estimation of pitching moment coefficient of the fuselage.